Studies on the suitability of tomato (Solanum lycopersicum L.) varieties for protected cultivation - Ravi Gautam; Praveen K. Singh; B. S. Tomer; Zakir Hussian; A.K. Singh; Shalini Gaur Rudra; Sandeep Kumar Lal; Jugendra Kumar (Annals of Agricultural Research, 2024)
The genetic variability, estimation of character association between yield and its component traits by correlation and genetic divergence was studied in 36 genotypes for 16 quantitative and qualitative traits. The genotypes were evaluated under protected environment at Centre for Protected Cultivation and Technology, ICAR-IARI, New Delhi for two consecutive years during 2018 and 2019. The analysis of variance exhibited significant genotypic differences, showing considerable amount of genetic variability among different genotypes. Among the cherry group, genotypes 264 and 305 were found promising for yieldtraits whereas genotypes 178 and 115 were found promising for both yield and quality traits in non-cherry group. The yield per1000 sq. m. showed significant positive correlation with average fruit weight (g), pericarp thickness (cm), polar diameter of fruit (cm), equatorial diameter of fruits (cm), fruit weight uniformity within cluster (g) and average fruit weight after each harvest (kg).